A dual-gate field-effect transistor in graphene heterojunctions. (February 2021) - Guo, Lingling; Zhang, Qingtian; Chan, Kwok Sum
Abstract: We propose a dual-gate field-effect transistor in graphene under the irradiation of off-resonant circularly polarized light. Graphene heterojunction is created by tuning the carrier densities in graphene through a top gate and back gate. The conductance of the graphene heterojunction oscillates periodically with the top and back gate voltages due to the Fabry-Perot resonances. It is found that the proposed device can act as a promising field-effect transistor, and the "on" and "off" states are controlled by the gate voltages and the off-resonant circularly polarized light. Comparing our simulation results with the experimental results, we find that our theoretical calculations agree well with the reported experiments. Our theoretical simulation enables new possibilities for the design of a photon controllable field-effect transistor in graphene, and it can also work as an optical sensor. Highlights: A promising field-effect transistor is proposed in graphene heterojunctions. The carrier densities of the device are tuned by the gate voltages, and a graphene heterojunction is created. The "on" and "off" states of the transistor are controlled by the gate voltages and the laser irradiation. The theoretical simulations agree well with the reported experiments.